Studi Pengaruh Faktor Suhu, Waktu, Massa Katalis dan Perbandingan Mol Dalam Produksi Biodiesel Dari PFAD Menggunakan Katalis Karbon Tersulfonasi - Naka Yura; Umar Kalmar Nizar (Departemen Kimia FMIPA UNP, 2020)
Depletion and environmental problems caused by the use of fossil fuels, the need for alternatives to balance the availability of nature. Biodiesel synthesis has become a concern lately for renewable and sustainable fuels. In this work, biodiesel is synthesized from 5 different acid catalysts with the use of the same raw material, PFAD. Catalysts used for biodiesel synthesis are acid catalysts from glucose derivatives (D-glucose) acid catalysts from starches, acid catalysts from empty fruit bunches, acid catalysts from oil palm and bamboo branches, and acidic catalysts from glucose modified with oscillation flow. Acid catalyst from glucose derivative (D-Glucose) obtained conversion of FFA and FAME respectively 95.4% and 92.3% with the optimum reaction conditions was 2.5% of the catalyst mass, 10: 1 mole ratio of PFAD methanol, reaction temperature 75 C and reaction time for 2 hours. Acid catalyst from starch obtained conversion of FFA and FAME respectively were 94.6% and 90.4% with the optimum reaction conditions ie 2% mass of catalyst, 10: 1 mole ratio of PFAD methanol, reaction temperature of 75C and reaction time of 2 hours. Acid catalyst from empty fruit bunches obtained 98% FFA conversion with optimum conditions of 4% catalyst mass, 16: 1 mole ratio of PFAD methanol, reaction temperature of 100 C, time of 3 hours. Acid catalysts from oil palm and bamboo shells have FFA conversion and different FAME values, namely 97% and 95% for CKS, while 95.8% and 94.2% for bamboo with the same optimum conditions at 4% catalyst mass, 15: 1 comparison mole of methanol, temperature 65 C, reaction time 1 hour. And acid catalyst from glucose modified by oscillation flow gets FFA and FAME conversion of 97% and 94.21% with optimum reaction conditions, 2.5% of catalyst mass, 9: 1 mole ratio of methanol, temperature of 60C and reaction time for 50 minute.